Tasks Oriented Towards the Use of Operational–Practical Methods in Textbooks for Environmental Studies (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The choice of textbook is important to the quality of the educational process as the textbook is the most frequently chosen teaching material in environmental studies. It should align with didactic recommendations encouraging an active role for students in the educational process, which is facilitated using operational–practical methods. The research aimed to examine the tasks in the textbooks for environmental studies and to identify those oriented towards operational–practical work. The research sample included textbooks from four publishing houses. The study used a descriptive non-experimental method of pedagogical research. We separately analysed the textbooks from each of the four publishers for each grade. The results show that the presence of tasks oriented towards operational–practical methods vary by grade and publisher. The largest number of tasks focusing on the use of operational–practical methods was found in the textbooks for third grade, followed by first and second grade.